The Lavender Vote Lesbians, Gay Men, and Bisexuals in American Electoral Politics - Hertzog, Mark (NYU Press, 1996)
In the quarter century since the Stonewall riots in New York City's Greenwich Village launched the national gay-rights movement in earnest, LGB voters have steadily expanded their political influence. The Lavender Vote is the first full- length examination of lesbians, gay men, and bisexuals as a factor in American elections. Mark Hertzog here describes the differences in demographics, attitudes, and voting behavior between self-identified bisexuals and homosexuals and the rest of the voting population. He shows that lavender self- identifiers comprise a distinctive voting bloc equal in numbers to Latino voters, more liberal across the board on domestic social issues (though not necessarily on economic or national security issues) than non-gay voters, and extremely unified in high-salience elections. Further, lavender voters, contrary to popular belief, are up for grabs between the two major parties. Offering a clear and thorough explanation of LGB voting tendencies, this volume will be must-reading for elected officials, candidates for office, and all those interested in learning about LGB voters.